Relationship between biopsychosocial and spiritual factors with the readiness to quit smoking - Mohd Haazik Mohamed; Nor Aryana Hassan; Muhamad Hairul Nizam Abd Hamid; Fredie Robinson; Ismail Maakip; Peter Voo Su Kiong (Universiti Putra Malaysia, 2024)
Introduction: Understanding the readiness to quit smoking is essential to deliver the best quit-smoking services in Malaysia. Objective: This study was conducted to determine the relationship between biopsychosocial and spiritual factors and the readiness to quit smoking among Malaysian adults. Materials and methods: A cross-sectional study using convenience sampling was used in this study. A total of 389 smokers aged 18 years old and above who registered at jomquit.com website participated in this study voluntarily. Questionnaires such as the stages of change readiness and treatment eagerness scale for smoking cessation (SOCRATES-S), Fagerstrom test for nicotine dependence (FTND), depression anxiety stress scale (DASS), the multidimensional scale of perceived social support (MSPSS), and a modified version of functional assessment of chronic illness therapy - spiritual well-being for non-illness (FACITSP-Non-Illness) were used in this study. Results: The results of this study found that nicotine dependence, stress, anxiety, depression, and social support (family, friends, and significant other) have significant relationships with the early stage of readiness to quit smoking (domains of recognition and ambivalence (p<0.05). Anxiety, social support (family, friends and significant other), and spiritual well-being had a significant relationship with the end stage of the readiness to quit smoking (domain of taking action, p<0.05). Conclusion: This study conclusively showed that nicotine dependence, stress, anxiety, depression, social support, and spiritual well-being might potentially play crucial roles in the initial stages of readiness to quit smoking and the final stage of taking action towards quitting. Therefore, emphasising the significance of including these variables in programmes aimed at helping people quit smoking is noteworthy